Finding “What's Wrong With Us”: Antibiotic Prescribing Practice Among Physicians in the United States - Rynkiewich, Katharina (Frontiers in Sociology, 2020)
Antibiotic stewardship – or the responsible use of antibiotics – has been touted as a solution to the problem of antibiotic resistance. Antibiotic stewardship in medical institutions attempts to change the antibiotic prescribing “behaviors” and “habits” of physicians. Interventions abound targeting “problem prescribers,” or those physicians whose practice is out of line with physician peers. Thus, the locus of decision-making in antibiotic prescribing is thought to be the found with the individual physician. Based on 18-months of participant observation and in-depth interviewing of antibiotic-prescribing physicians at two medical institutions in the United States, this paper will question notions of antibiotic stewardship that center on individual “behaviors” and “habits.” Many physicians have taken to heart a reductionist approach in studies of antibiotic prescribing, including several physicians I encountered during research who enthusiastically located the benefit of my research in the ability to identify “what’s wrong with us.” In this paper, I use two representative ethnographic case studies to argue that antibiotic stewardship interventions aimed at identifying and correcting “bad” physician practice limit the possibilities of understanding the social dynamics of the institution. Through an analysis of everyday encounters in the hospital setting, I show how decision-making in antibiotic prescribing can more productively be located between and among institutions, physicians, patient charts, and other hospital-based staff members (e.g. pharmacists, nurses). By demonstrating that antibiotic prescribing is a collective practice occurring through engagement with social and material surroundings, I argue that we can better account for the weighted ways in which social action and relations unfold over time.